Fostering the AR illusion: a study of how people interact with a shared artifact in collocated augmented reality - Yang, Jifan; Bednarski, Steven; Bullock, Alison; Harrap, Robin; MacDonald, Zack; Moore, Andrew; Graham, T. C. Nicholas (Frontiers in Virtual Reality, 2024)
Augmented Reality (AR) is a technology that overlays virtual objects on a physical environment. The illusion afforded by AR is that these virtual artifacts can be treated like physical ones, allowing people to view them from different perspectives and point at them knowing that others see them in the same place. Despite extensive research in AR, there has been surprisingly little research into how people embrace this AR illusion, and in what ways the illusion breaks down. In this paper, we report the results of an exploratory, mixed methods study with six pairs of participants playing the novel Sightline AR game. The study showed that participants changed physical position and pose to view virtual artifacts from different perspectives and engaged in conversations around the artifacts. Being able to see the real environment allowed participants to maintain awareness of other participants’ actions and locus of attention. Players largely entered the illusion of interacting with a shared physical/virtual artifact, but some interactions broke the illusion, such as pointing into space. Some participants reported fatigue around holding their tablet devices and taking on uncomfortable poses.